2012
DOI: 10.3382/ps.2012-02277
|View full text |Cite
|
Sign up to set email alerts
|

Egg production curve fitting using nonlinear models for selected and nonselected lines of White Leghorn hens

Abstract: Egg production curves describe the laying patterns of hen populations over time. The objectives of this study were to fit the weekly egg production rate of selected and nonselected lines of a White Leghorn hen population, using nonlinear and segmented polynomial models, and to study how the selection process changed the egg-laying patterns between these 2 lines. Weekly egg production rates over 54 wk of egg production (from 17 to 70 wk of age) were measured from 1,693 and 282 laying hens from one selected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
4
19
1
5
Order By: Relevance
“…If the broody hen is allowed to incubate the eggs the length of pause extends to 121.75d. The analysis of egg production in indigenous chicken revealed a shift in the pattern with delayed peaking compared with breeds like White Leghorn (Savegnago et al, 2012). The number of eggs per cycle in the present study was higher than the previous reports (FAO, 2009) but comparable with that of Iqbal and Pampori (2008).…”
Section: Discussioncontrasting
confidence: 64%
“…If the broody hen is allowed to incubate the eggs the length of pause extends to 121.75d. The analysis of egg production in indigenous chicken revealed a shift in the pattern with delayed peaking compared with breeds like White Leghorn (Savegnago et al, 2012). The number of eggs per cycle in the present study was higher than the previous reports (FAO, 2009) but comparable with that of Iqbal and Pampori (2008).…”
Section: Discussioncontrasting
confidence: 64%
“…However, none of these studies reported on optimizing the egg production parameters of Boschveld indigenous chicken from 21 week until 44 weeks of lay. Savegnago et al (2012)recorded that non-linear regression and multi-stage modelling methods couldbe used in modelling egg production. Among the non-linear regression models, Adams-Bell and logistic are reputed to be good egg production models, with the Adams-Bell model or a simple linear regression exhibiting better fitting performance from peak production to 20 or 24 weeks of production (Faridi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of MME is that the statistic not only evaluates the goodness of fit of a model, but also reflects the direction in which observed values deviate from predicted values (Savegnago et al , 2012). A positive MME means that the model overestimates the egg production rate as a whole; correspondingly, a negative MME indicates that the egg production rate is underestimated.…”
Section: Methodsmentioning
confidence: 99%